Indigenous knowledge in Cirebon city's road toponymy - Damayanti, Herlinah; Savitri, Indri; Kurnia, Maya Dewi; Meinindartato, Weli (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The purpose of this study was to describe road toponymy in Cirebon City, identify the origin of road toponymy in Cirebon City, and identify local wisdom in toponymy in Cirebon City. This research examines the local wisdom of road toponymy in Cirebon City. Local wisdom is a form of agreement that becomes a legacy for guidance in social life and can be a benchmark for building civilization and the personal identity of the nation, as well as selecting global culture. The methods of research use qualitative methods with an anthropolinguistic approach. The research data collected are street names in the city of Cirebon. The source of data obtained in the form of street names in Cirebon City contains local wisdom. Data collection methods used were observation, interview, and documentation methods. Data collection techniques include reading, note-taking, and interview techniques. The data analysis technique used was the intralingual pairing method. The results showed that there are 21 street names in Cirebon City. The road names in Cirebon City tend to be influenced by social aspects rather than physical aspects. Street names that contain historical stories and local wisdom in them include Karanggetas, Kanggraksan, Pesayangan, Panjunan, and Lemahwungkuk. Meanwhile, street names influenced by place or building names include Pasuketan, Parujakan, Talang, Kebon Belimbing, and Kolektoran. According to 21 names of streets in Cirebon City, there are only 9 street names that have local wisdom, namely Road Talang, Road Panjunan, Road Pesayangan, Road Pulasaren, Road Sukalila, Road Pekalangan, Road Karanggetas, Road Pekarungan, and Road Larangan.